Enhance dimension accuracy of a thin-walled plastic part by combining simulation and design of experiments - Huynh, Đỗ Song Toàn; Tran, Minh Thế Uyên; Nguyen, Danh Kiên; Le , Hiếu Giang (Journal of Technical Education Science, 2015)
One of the main objectives of the injection molding technology is to improve the quality of plastic products and shorten product cycles, reduce production costs. The determination of the optimal parameters of injection molding process has a great influence on productivity, quality and cost of production of plastic mold industry. Therefore, in order to improve the quality of plastic products by optimizing the parameters of injection molding applications experimental planning method, the paper "Enhance dimension accuracy of a thin-wall plastic part by combining simulation and design of experiments" is necessary. The outcomes of this paper are completed the analysis and experimental simulation of a thin-walled injection molding plastic product with different injection molding parameters. Experimenting to find out the optimal parameters (the optimal set) for the non-flow dimension error is lowest, then evaluating corresponding simulation results to the optimum parameters of the actual injection. As a result, this paper proposes the simulation plans with different parameters, the parameters that correspond to the optimal set are recommended to implement.